A afetividade na prática pedagógica de professores do ensino médio sob a ótica dos discentes - Benda, Juliana (2015)
The subject of this research is the affection in the pedagogical practice of high school teachers from the perspective of students. Aimed at analyzing, under the perspective of the student, if the affection in the pedagogical practice of high school teachers facilitates the learning process. The specific objectives are listed as follows: check which aspects related to affection are listed by students and consider whether, in their view, teachers use their experiences in the classroom. We seek to answer the following questions: How does the affection in the pedagogical practice of high school teachers facilitate in the students' learning process? Are the subjects that students like more or less related to the teacher's stance? Do high school teachers establish a closer relationship with teenage students to understand their needs and prioritize their life experiences to articulate the curriculum content? Reflecting on the informal conversations we had with teenage students, in which they pointed out their lack of interest in studies, since most have difficulty in reading, writing and interpreting texts in addition to the traditional teaching methodology used by many teachers as pointed out in this thesis' presentation, we start from the assumption that many high school teachers apply the school content totally disconnected from the student's reality, and do not establish a closer relationship with the students, thus hindering the learning process. The research universe was a state public school located in the north of São Paulo city. The subjects were six students who attend high school, two of the first year, two the second year and two of the third year. We use a qualitative approach methodology, whose data collection instrument was the semi-structured interview and analysis of the legislation governing the secondary education, such as: the National Education Plan, the National Curriculum Parameters for Secondary Education, the National Curriculum Guidelines for Secondary Education, the Law of National Education Guidelines and Bases and the Secondary Education Curriculum. The interview data was reviewed according to the content analysis proposed by Bardin. As a theoretical framework we use the following authors: Teixeira (1968), Castro (2009), Fernandes (2009), Nascimento (2007) to support the secondary education category; Paulo Freire (2000, 2003, 2004), and Vygotsky (1998, 1999) to support the affection category. Through interviews with the students, we listed three categories: positive and negative attitude of teachers on students, banking education and motivation on the part of teachers and students. On the first category, we find that the students have an easier time learning when teachers interact with them, when they give voice to the students in class by answering their questions, when they use a proper language, and especially when they respect their individuality. As for the second category, students complain of banking classes, in which the teacher is the only one speaking or just telling them to copy the activities, and does not allow students to express themselves and; as for the third category, the students are aware that the motivation for learning also has to come from them, but that often teachers do not cooperate, as they are unmotivated themselves.